mRNA-Based Biomarker Identification for Targeted Therapy Development in Pancreatic Cancer - Saima Firdaus; Rafat Parveen (Biology and Life Sciences Forum)
Pancreatic cancer is one of the highly malignant cancers that have poor prognosis and limited treatment options. The development of targeted therapies is important for improving patient outcomes. In this study, we analyzed the datasets from the GEO database to identify potential mRNA biomarkers for pancreatic cancer. Differentially expressed gene (DEG) analysis was performed in R to identify genes that expressed differentially between tumor and normal samples. TFF1 and LAMC2 emerged as key candidate genes for pancreatic cancer among the identified DEGs. Additionally drugs approved by the FDA were repurposed as an inhibitor against key genes. These findings suggest that these genes play a significant role in pancreatic cancer progression and have the potential to serve as molecular elements for targeted therapies.